The effect of future time orientation on employees’ achievement motivation: Peran orientasi masa depan terhadap motivasi berprestasi karyawan - Helen Angelica; Winida Marpaung (Talenta Publisher, 2020)
The present study examines the role of organizational employees' future time orientation toward their achievement motivation. Using a cross-sectional design, the results of the present study showed that employees who possess a high degree of future time orientation were more likely to possess a higher degree of achievement motivation than participants with lower future time orientation. We discuss the importance and the importance of promoting future time orientation among organizational employees. Penelitian ini menelaah hubungan antara orientasi masa depan terhadap motivasi berprestasi karyawan organisasi. Dengan menggunakan desain cross-sectional, hasil penelitian ini menunjukkan bahwa karyawan yang memiliki derajat orientasi masa depan yang tinggi cenderung memiliki derajat motivasi berprestasi yang lebih tinggi daripada karyawan yang memiliki orientasi masa depan yang rendah. Diskusi kami fokuskan mengenai pentingnya orientasi masa depan pada karyawan dan bagaimana cara memotivasi karyawan untuk meraih prestasi yang diinginkan.